Regulating corporate human rights violations : humanizing business - Deva, Surya (London : Routledge, 2012)
Despite the continuous addition of regulatory initiatives concerning corporate human rights responsibilities, what we witness more often than not is a situation of corporate impunity for human rights abuses. The Bhopal gas leak - examined as a site of human rights violations rather than as a mass tort or an environmental tragedy - illustrates that the regulatory challenges that the victims experienced in 1984 have not been overcome so far. This book grapples with and offers solutions to three major regulatory challenges to obligating companies to comply with human rights norms whilst doing business, and asks; why companies should adhere to human rights, what these responsibilities are, and how to ensure that companies comply with their responsibilities. Building on literature in the fields of law, human rights, business ethics, management, regulation and philosophy, this book proposes a new'integrated theory of regulation' to overcome inadequacies of the existing regulatory framework that seeks to humanize business'--Provided by publisher.
Machine generated contents note: 1. Introduction -- 2. Understanding'Bhopal' afresh -- 3. Evaluation of existing regulatory initiatives -- An analytical framework -- 4. Existing regulatory initiatives -- An evaluation of (in)adequacy -- 5. Just profit or just profit -- Why should corporations have human rights obligations? -- 6. How to behave in Rome? Determining standards applicable to MNCs -- 7. The integrated theory of regulation -- A critical response to'responsive regulation' -- 8. Vision of an integrated framework of corporate regulation -- 9. Conclusion.
Includes bibliographical references (pages 241-264) and index.
Keywords: Corporations -- Moral and ethical aspects; Social responsibility of business; Corporate governance -- Law and legislation; Human rights; Corporations -- Corrupt practices